Intervensi Komunitas: Mewujudkan Perubahan Sosial Lembaga Masyarakat Desa Hutan Konservasi (LMDHK) “Wono Mulyo”Menuju Kemandirian Lembaga - Diah Psupaningrum; Ati Kusmiati (UNEJ e-Proceeding, 2018)
Community empowerment approach should play role in improving human resourcesespecially in establishing and changing the community behaviour to achieve more quality livingstandard. The research aimed to participatory develop the capacity of Lembaga Masyarakat DesaHutan Konservasi (LMDHK) (Conservation Forest Village Community Institution)―Wonomulyo‖ through institutional social change in realizing institutional independence. Theresearch used qualitative approach with subject emancipation research approach. Locationdetermination method was conducted using purposive method, which was at Wonoasri Village,Tempurejo Sub-district, Jember Regency, East Java Province. Data source in the research waswords and actions of the key informants/stakeholders consisted of the administrators and membersof the Conservation Forest Village Community Institution as well as rehabilitation land farmers.Data collection obtained primarily from the result of observation, in-depth interview, and focusgroup discussion (FGD) as well as PRA (Participatory Rural Appraisal) method to conductinstitutional development. Data analysis used interactive model from Miles and Huberman. Theresearch results found that community intervention program on Conservation Forest VillageCommunity Institution was conducted through participatory research. The capacity building ofLMDHK ―Wono Mulyo‖ was conducted through self-learning process and building independentinitiatives. Therefore, independence development was a form of social change of human beingsfrom a situation that depended on aid to become more independent based on initiatives andcreativities of the local communities.